Case Study of a Small Scale Reverse Osmosis System for Treatment of Mixed Brackish Water and STP Effluent - Widiasa, I Nyoman; Jayanti, Retno Dwi (Journal of Engineering and Technological Sciences, 2017)
A case study on utilizing reverse osmosis (RO) technology to fulfill fresh water needs at a mall and a hotel has been done on Bali Island, Indonesia. A mix of brackish water and sewage treatment plant (STP) effluent was used as feed water in the RO system. The system used 36 membrane elements (CSM RE 8040 BLN) arranged into two stages: 8 pressure vessels (PVs) in the first stage and 4 PVs in the second stage, each loaded with 3 membranes. The objectives of this research were to assess the cleaning effectivity in the plant, to evaluate the cleaning of 1 membrane element using a CIP system, and to assess the use of the membrane for filtration in the pre-treatment system. SEM and FTIR analysis indicated that the foulants on the membrane surface were dominated by organic foulants and inorganic deposits. To clean the discarded membrane the proposed method used NaOH solution (pH 12 and pH 13) and citric acid (pH 2 and pH 3). All membranes displayed a dramatic decline in rejection of about 80%. Based on the rejection tests of SO42-, Cl-, turbidity reduction approached 100%. It can be concluded that an RO membrane that has undergone selectivity decline can be re-used as a filtration membrane in the pre-treatment system.